Qualidade de sementes, micropropagação, conservação in vitro e isolamento de DNA genômico de Luehea divaricata Mart. & Zucc. - León, Enrique Asterio Benítez (2014)
Luehea divaricata Mart. & Zucc., is a native species, found in the Atlantic Forest and Pampa biomes in Rio Grande do Sul state, Brazil, belonging to the Malvaceae family. Considering the need for recovery and restoration of degraded areas, the demand for seeds and seedlings of native species may register significant increases, and the contribution of research studies to native species will be of great importance for both the forestry and the environmental sectors. This study aimed to research the quality of seeds, the development of methodologies for micropropagation and in vitro conservation of Luehea divaricata and isolation of genomic DNA of the species. Physiological and sanitary quality tests of seeds stored in Kraft paper inside refrigerator, in two different periods, collected from different places of its natural habitat, were conducted. The development of methodologies for micropropagation studies were divided in different experiments, testing at first, the response of cultures initiated from epicotyl, to stimuli from different sources and concentrations of cytokinin on in vitro multiplication. Afterwards, the pulse effect treatment with concentrations of IBA on the rooting ability of in vitro nodal segments cultivated in nutrient medium MS or WPM were tested both presence or absence of activated charcoal. For acclimatization of micropropagated plants, the effect of different concentrations of sucrose in the nutrient medium WPM and two kinds of commercial substrates were evaluated. The effect of the, osmotic regulator, mannitol, presence or absence sucrose, on the performance of in vitro nodal segments, aimed at in vitro conservation of germplasm was also observed. Three protocols were tested to isolate genomic DNA from young leaves, proving its efficiency and quality by spectrophotometry quantification and digestion with the Hind III restriction endonuclease. The main results show that genotypes differ both in their physiological and sanitary quality, and maintain their viability after six months of storage in a refrigerator. For in vitro multiplication of nodal segments, the addition of cytokinins to the nutrient medium is dispensable ,and when added, promote callus formation, unwanted at such stage. The rooting of nodal segments is successful in nutrient medium WPM in the absence of activated charcoal and it was found that the pulse treatment with IBA concentrations exceeding 9μM may optimize the process. The concentration of 30 g L-1 sucrose in the nutrient medium WPM is effective in develop plants capable of acclimatization using either commercial substrate Mecplant® or H-Decker®. It is possible in vitro conservation of nodal segments under minimal growth for a period of 120 days with the use of mannitol combined with sucrose concentrations of up to 15 g L-1 in the nutrient medium ½MS. The DNA isolated protocols were effective to obtain DNA concentration and quality still with the presence of proteins and polysaccharides. The results may contribute to the existing information on the in vitro propagation of Luehea divaricata, supporting breeding programs, germplasm conservation and analysis of genetic variability in natural populations.